Synthesis and Photoluminescence Properties of Li2SrSiO4 Activated with Dy3+ and Sm3+ - Erdoğmuş, Ertuğrul; Erdoğmuş, Ertuğrul (Springer, 2015)
Li2SrSiO4:M (M: Dy3+ and Sm3+) phosphors were synthesized by the conventional solid state reaction. The synthesized materials were characterized by powder XRD. The emission and excitation spectra of these phosphors were measured at room temperature with a spectrofluorometer. The first phosphor, Li2SrSiO4:Dy3+, emits at 479, 573, and 666 nm upon 351 nm excitation. The second phosphor, Li2SrSiO4:Sm3+, emits at 561-571, 594, 647-655, and 703-713 nm upon 399 nm excitation. Also, the dependence of the photoluminescence properties of both phosphors on boric acid concentration was investigated. The results showed that boric acid was effective in improving the photoluminescence intensity of both phosphors.
Keywords: Luminescence; X-Ray Diffraction; Inorganic Borate; Boric Acid